Effect of Biochar from Urban Waste and Eco-enzymes on Growth and Yield of Shallots (Allium ascalonicum, L) - Elisabet Restiana Jaya; Yohanes Parlindungan Situmeang; Anak Agung Sagung Putri Risa Andriani (Warmadewa University Press, 2021)
Abstract This study aims to determine the effect of biochar dose from urban waste and the concentration of eco-enzymes and their interactions on the growth and yield of shallots. The research was carried out in the greenhouse of the Faculty of Agriculture,Warmadewa University with an altitude of 25 m above sea level, and took place from April to June 2021. This study used a factorial randomized block design method consisting of two factors. The first factor is the dose of biochar with 4 levels (0; 5; 10; and 15 tons ha-1), while the second factor is the concentration of eco-enzyme which consists of 4 treatment levels (0; 7.5; 15.0; and 22.5 ml l-1). The results showed that the interaction between the dose of biochar and the concentration of eco-enzyme had a significant effect on the fresh weight of the stover per clump and had a very significant effect on the dry weight of the stover per clump, but had no significant effect on other variables. The treatment dose of biochar and eco-enzyme had a very significant effect on all observed variables. The results showed that the biochar and eco-enzyme treatments had a very significant effect on all observed variables. The application of biochar and eco-enzyme has a very significant effect on all observed variables. The provision of biochar treatment from urban waste was able to increase the fresh weight of tubers in the 15-ton ha-1 treatment, which was an increase of 39.40% compared to without biochar, while the highest fresh fruit weight was obtained in the eco-enzyme treatment of 22.5 ml l-1, which increased by 29.77% compared without eco-enzyme. Keywords: Biochar; urban waste; eco-enzyme; shallots